Glucosamine administration in athletes: Effects on recovery of acute knee injury - Ostojic, S. M.; Arsic, M.; Prodanovic, S.; Vukovic, J.; Zlatanovic, M. (Research in Sports Medicine, 2007)
The main aim of this study was to examine the effects of 4 weeks of glucosamine administration on the functional ability and the degree of pain intensity in competitive male athletes after acute knee injury. This study was a randomized, double-blind parallel trial of glucosamine (1500 mg per day) or a placebo for 28 days, utilising 106 patients with an acute knee injury. Pain and functional ability were evaluated at the beginning of the study and at 7, 14, 21, and 28 days after starting treatment. Pain intensity at rest and while walking was assessed using a visual analog scale. Passive knee flexibility (flexion and extension) of the injured limb was measured using a modified goniometer, and the degree of knee swelling was measured and compared with the noninjured limb. No significant difference was found between the glucosamine, and placebo group in mean pain intensity scores for resting and walking, and degree of knee swelling at the 7-day, 14-day, 21-day, and 28-day assessment. There was no significant difference between passive knee flexibility at the 7-day, 14-day, and 21-day assessment. After 28 days of treatment the patients from the glucosamine group demonstrated significant improvement in knee flexion and extension as compared with the placebo group.